'How do I choose?': mathematics teachers' sensemaking about pedagogical responsibility. (27th May 2021) - Chen, Grace A.; Marshall, Samantha A.; Horn, Ilana S.
ABSTRACT: Teachers' decisions are often undergirded by their sense of pedagogical responsibility: whom and what they feel beholden to. However, research on teacher sensemaking has rarely examined how teachers reason about their pedagogical responsibilities. The study analysed an emotional conversation among urban mathematics teachers about what they teach mathematics for, given the many non-mathematical challenges they and their students face. The familiarity and simplicity of love and life skills narratives deployed to describe what it means to be a good teacher and to do good teaching may be comforting, but limit teachers' engagement with other authentic forms of pedagogical reasoning about their pedagogical responsibility in complex sociopolitical contexts. The findings reveal the importance of opportunities to explore alternate possibilities 'for what, ' especially within structured and supportive teacher collaborative groups.